Pengelolaan Usaha Mikro Kecil dan Menengah (UMKM) Tenun Sarung Sambu’ Khas Kabupaten Mamasa - Intan Timur; Levina Levina (Politeknik Raflesia Press, 2025)
This study aims to determine the factors that influence the management of Micro, Small and Medium Enterprises of Sambu Sarong Weaving in Mamasa Regency. This study uses a qualitative descriptive method. The informants in this study were one of the MSME entrepreneurs of Sambu Sarong Weaving and members of MSMEs in Mamasa Regency. The data for this study were collected by directly interviewing the research informants. The analysis used in this study is a qualitative descriptive analysis. The results of this study indicate that the factors that support the management of MSMEs of Mamasa Sambu Sarong Weaving are the financial recording process, product promotion and the process of making sambu sarong weaving.